Association between asthma and work absence in working adults in the United States. (3rd June 2023) - Jacob, Louis; Shin, Jae Il; López-Sánchez, Guillermo F.; Haro, Josep Maria; Koyanagi, Ai; Kostev, Karel; Butler, Laurie; Barnett, Yvonne; Oh, Hans; Smith, Lee
Abstract: Objectives: The present study aimed to investigate the association between asthma and work absence in a large sample of US working adults, while controlling for several sociodemographic and health characteristics. Methods: This study used data from the 2019 Health and Functional Capacity Survey of the RAND American Life Panel (ALP). Work absence corresponded to the number of days of absence from work for health-related reasons in the past 12 months. Current asthma was self-reported and was included in the analyses as a dichotomous variable. Control variables included sex, age, ethnicity, marital status, education, occupation, annual family income, health insurance, and number of chronic physical or psychiatric conditions. Finally, the association between asthma and work absence was analyzed using logistic regression models. Results: This study included 1, 323 adults aged 22–65 years (53.1% males; mean [SD] age 43.1 [11.7] years). Individuals with asthma were more likely to report at least one (81.5% versus 56.8%, p -value<0.001) or three days of absence (56.9% versus 31.3%, p -value=0.003) from work in the past 12 months than those without asthma. These findings were corroborated in the regression analyses, as asthma was positively and significantly associated with work absence after adjusting for all control variables (at least one day of absence: OR=3.24, 95% CI=1.44–7.29; at least three days of absence: OR=2.61, 95% CI=1.26–5.40). Conclusions: This US study of working adults showed that asthma was a risk factor for work absence. Further research is warranted to better understand the factors predisposing to work absence in the asthma population.